Value of animal traceability systems in managing a foot-and-mouth disease outbreak in southwest Kansas - Pendell, Dustin Lester (Kansas State University, 2006)
Concerns regarding management of animal disease and related perceptions about food safety have escalated substantially in recent years. Terrorist attacks of September 2001, discovery of bovine spongiform encephalopathy in a dairy cow in December 2003 in Washington state and subsequent discoveries of BSE infected animals in Texas in 2005 and Alabama in 2006, and recent worldwide outbreaks of highly contagious animal diseases (i.e., Foot-and-Mouth Disease and Avian Influenza A (H5N1)) have made apparent the need for animal traceability in U.S. livestock production and marketing. In addition, animal identification and trace-back systems are rapidly developing throughout the world increasing international trading standards. In recent years, increasing numbers of economic analyses of animal diseases have integrated epidemiological models into economic frameworks. However, there are only a few studies that have used this integrated framework to analyze the effects of animal traceability on highly contagious animal diseases. This study’s goal is to quantify and evaluate the economic impacts of different depths of animal identification/trace-back systems in the event of a hypothetical highly contagious foot-and-mouth disease outbreak that poses a threat to U.S. livestock competitiveness. Specifically, an epidemiological disease spread model is used to evaluate the impact of a foot-and-mouth disease outbreak in southwest Kansas. The information obtained from the disease spread model is then used in conjunction with an economic model to determine the changes in welfare of producers and consumers. Results obtained from the epidemiological model indicate that as the depth of animal identification in cattle is increased, the number of animals destroyed is reduced as are the associated costs. Also, the length of the outbreak is reduced by approximately two weeks. The economic results suggest that as surveillance is increased, decreases in producer and consumer welfare are smaller. Furthermore, as surveillance is increased, decreases in producer and consumer surplus measures can be reduced by approximately 60 percent.
Keywords: Animal identification; Equilibrium displacement model; Foot-and-mouth disease; Traceability; Economics, Agricultural (0503)